Original paperNon-ST elevation myocardial infarction related to total coronary artery occlusion – prevalence and patient characteristics - Roleder, Tomasz; Smolka, Grzegorz; Pysz, Piotr; Kozyra, Andrzej; Ochała, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Acute coronary occlusion (ACO) may also present as non-ST elevation myocardial infarction (NSTEMI) and thus veil the real threat. Aim: Based on combined analysis of electrocardiography and echocardiography findings, we aimed to describe profile of NSTEMI patients at increased risk of ACO. Material and methods : It was a retrospective study that included patients referred for cardiac catheterisation due to NSTEMI. Patients were selected into the study in two different time frames. Firstly, all consecutive NSTEMI patients were enrolled in a 12-month period to detect the prevalence of ACO (prevalence group). Secondly, all NSTEMI patients with ACO hospitalized in the previous 5 years were also enrolled (NSTEMI-ACO group). All patients had 12-lead electrocardiogram (ECG) and the transthoracic echocardiography (TTE) performed before the cardiac catheterisation. Results: Fifty-three consecutive patients (37 males) were enrolled into the prevalence group in a 12-month period. Ten (19%) of them were diagnosed with ACO. Thirty-four consecutive patients were enrolled into the NSTEMI-ACO group. Non-ST elevation myocardial infarction patients with ACO were younger as compared to NSTEMI patients without ACO. Non-ST elevation myocardial infarction patients with ACO were less likely to have anterior wall ischaemia as detected by ECG, which was not reflected by TTE results. Combined assessment of ischaemia by ECG and impaired contractility by TTE did not reveal any significant differences between NSTEMI patients with or without ACO. Conclusions : The identification of NSTEMI patients with ACO is challenging. Therefore, the utmost caution should be paid to prevent delay of coronary angiography in NSTEMI patients who have increased risk of ACO.